MENGELOLA KEUNGGULAN POSITIONING TOKO (STORE POSITIONING ADVANTAGE) (STUDI EMPIRIS : HYPERMART AMBON) - Els Jossi Kliwas; R. H. Sitaniapessy; S. Saptenno (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to test and analyze the effect of promotional discounts onstore image differentiation and store positioning advantage and its impact on theperformance of Ambon Hypermart stores. The sample in this study are consumerswho have visited Ambon Hypermart. Data was collected through distributingquestionnaires to 150 respondents using purposive sampling technique. While thedata analysis (Path Analysis).The results show that Promotional discounts have a positive andsignificant influence on Store Image Differentiation and Store PositioningAdvantages. It was also found that Store Image differentiation and StoreAdvantages had a positive and significant effect on the Performance of AmbonHypermart Store.